2014
DOI: 10.1111/rec.12059
|View full text |Cite
|
Sign up to set email alerts
|

Interim Response of Wading Birds (Pelecaniformes and Ciconiiformes) and Waterfowl (Anseriformes) to the Kissimmee River Restoration Project, Florida, U.S.A

Abstract: Success of the Kissimmee River RestorationProject will be evaluated in part by monitoring populations of wading birds (Pelecaniformes and Ciconiiformes) and waterfowl (Anseriformes). These two waterbird guilds were integral components of the pre-channelization river-floodplain ecosystem, and both declined substantially following channelization. Restoration is expected to attract wading birds and waterfowl by reintroducing naturally fluctuating water levels, seasonal hydroperiods, and historic vegetation commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Many wild species use riverine and floodplain habitats for one or more life history stages. For many species, even the immediate, direct effects of river management decisions are still poorly understood (Arias et al, 2013;Cheek et al, 2014;Strayer and Dudgeon, 2010), but our results suggest that subtle, long-term effects also may occur. Given expected increases in the intensity of management of rivers and other freshwater systems (Strayer and Dudgeon, 2010;Vorosmarty et al, 2010), a deeper understanding of the multiple effects of river management actions is needed.…”
Section: Conservation Implicationsmentioning
confidence: 67%
“…Many wild species use riverine and floodplain habitats for one or more life history stages. For many species, even the immediate, direct effects of river management decisions are still poorly understood (Arias et al, 2013;Cheek et al, 2014;Strayer and Dudgeon, 2010), but our results suggest that subtle, long-term effects also may occur. Given expected increases in the intensity of management of rivers and other freshwater systems (Strayer and Dudgeon, 2010;Vorosmarty et al, 2010), a deeper understanding of the multiple effects of river management actions is needed.…”
Section: Conservation Implicationsmentioning
confidence: 67%
“…Historical contingencies from early disturbances, the potential for alternative endpoints, and the successional timeframe for soil development belie assumptions that provide the basis for several myths that have clouded the science and practice of restoration ecology (Hilderbrand et al ). Mixed responses to the ongoing Kissimmee River restoration effort, including progress (Toth & van der Valk ; Colangelo ; Koebel et al ; Toth ) and shortcomings (Toth ; Cheek et al ; Spencer & Bousquin ), indicate elements of restoration projects with broad, ecosystem scale goals (e.g. ecological integrity) will have inconsistent temporal trajectories that need to be considered in evaluation and adaptive management plans (Suding ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rampant colonization and spread of H. altissima, H. amplexicaulis, and U. mutica suggests that the invasion of these exotic grass species could represent an alternative stable state (Holling 1973;Beisner et al 2003;Kulmatiski 2006) for the restored floodplain. Although avian use of the reflooded floodplain has exceeded expectations for reestablishment of functional habitat for wading birds (Cheek et al 2014), acceptance of exotic plant communities has wide-ranging ecological implications (Gordon 1998;Simberloff & von Holle 1999;D'Antonio & Meyerson 2002;Ewel & Putz 2004;Ricciardi et al 2013;Bernard-Verdier & Hulme 2015) and clearly conflicts with the ecological integrity goal for restoration of the Kissimmee River. Alternatively, if further intervention (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ecological response metrics are not standardized (Brown et al 1997;Zedler 2000;Matthews & Spyreas 2010;Faulkner et al 2011;Tapp & Webb 2015). Several studies (Weller 1995;Kingsford 1999;Cheek et al 2014) reported avian abundance and diversity can be an important outcome metric for evaluating restoration of wetland ecosystems. Moreover, certain avian taxa, such as waterfowl and other waterbirds, are ecologically, environmentally, esthetically, and economically valued by humans and thus important to monitor and convey results of restoration to stakeholders (Grado et al 2001(Grado et al , 2011Fleming et al 2015).…”
Section: Introductionmentioning
confidence: 99%